Numerical optimization of the extra-cavity diamond Raman laser in the multi-phonon absorption band - Shao, Zhenhua; Li, Bei; Chen, Hongzhi; Cao, Jun (Frontiers in Physics, 2022)
The physical process of Stimulated Raman scattering (SRS) in the diamond and the performance of the Raman laser in the multi-phonon absorption band of 2.5–3 μm were theoretical studied. A theoretical model for the external cavity diamond Raman laser emitting at waveband was built based on the Raman coupled-wave equation and boundary conditions. Raman laser output characteristics as lasing threshold, input-output and temporal behavior of Stokes conversion were investigated and theoretical simulated by varying the values of length of diamond and the transmittance of output coupler. The numerical modelling shows that to reduce the impact of the multi-phonon absorption and obtain the higher conversion efficiency, it is necessary to appropriate increasing the output coupling of the cavity. Taking the 3 μm diamond Raman laser optimization as an example, it is predicted that the conversion efficiency of 10% could be obtained with diamond length of 1cm, transmittance of 69% and pump intensity of 1.2 GWcm-2. The theoretical model also could be used to investigate other wavelength external cavity diamond Raman laser and helpful for the optimum design of diamond Raman lasers at mid-infrared band.